Long-term application of cattle manure alters functional N cycling genes and improves maize yield and nitrogen use efficiency - Yansheng Li; Muqing Liu; Zhenhua Yu; Changkai Liu; Xiaojing Hu; Junjie Liu; Jian Jin; Yuan Chen; Xingyi Zhang; Guanghua Wang; Xiaobing Liu (Geoderma)
Using livestock manure as organic fertilizer on farmlands has resulted in increased crop yields in many areas; however, the impact of long-term manure application on N cycling microorganisms and their effect on nitrogen utilization efficiency (NUE) associated with increased maize yield remains unclear. In this study, a long-term field trial was performed to compare four fertilization regimes: no fertilizer (CK), conventional synthetic fertilizer (CF), CF with 15 Mg ha−1 (FM1) and 30 Mg ha−1 (FM2) of dry-weight cattle manure, applied annually. After 10 and 12 years, FM1 and FM2 significantly boosted maize yield, especially after cycles of soybean–maize rotation, and improved NUE by 19–33 % and 17–53 %, respectively, compared with CF, with a positive correlation with increases in yield. Principal coordinate analysis showed that different fertilizer regimes were partitioned into four groups of N-related microbial communities. Proteobacteria, Actinobacteria, and Acidobacteria were the main phyla involved in N cycling. Among the genes involved in N cycling, gdhA, narB, nasD, norB, napA, nirB, nifA and hao demonstrated significant correlations with both plant N uptake and NUE. The insignificant differences between FM1 and FM2 in the relative abundance of most N genes in 2021 and 2023 helped to explain the similar crop outcomes between these two treatments. Compared with FM1, FM2 had a higher relative abundance of narG and a smaller size of constructed metagenome-assembled genomes (MAGs).